ANALISIS KEKUATAN SAMBUNGAN GESER GANDA ENAM JENIS KAYU PADA BERBAGAI SESARAN MENURUT DIAMETER DAN JUMLAH BAUT - Sucahyo Sadiyo; Imam Wahyudi; Fengky Satria Yoresta; . Nurhasanah; Muhammad Sholihin (PERENNIAL, 2012)
This research aims to determine the effect of double shear connection strength of six types of timber in various displacement based on diameter and the number of bolts. Six types of wood used are bangkirai, punak, meranti, sengon, bintangur and kapur. Double shear connection consists of the main member (wood) and side member (steel plate) with bolts connected. The average moisture content of sengon, meranti, bintangur and bangkirai are relatively similar (about 12 %), while kapur and punak are slightly higher at around 14 %. In contrast, the average density of six wood species are greatly vary ranging from the lowest sengon 0.26 g cm-3, to the highest 0.82 g cm-3 of bangkirai wood. The total load and load per bolt on double shear connection using bolts connector are influenced by the type of wood, diameter and number of bolts. There is a strong tendency that the higher specific gravity or density of the wood makes higher total load and load per bolt on double shear connection for each displacement. In addition, an increasing number of bolts makes the total load increased. On the other hand, it decreases load per bolts for each of bolts diameter. The use of 10 pieces of 7.9 mm diameter bolts on double shear connection for almost all type of wood produces the highest average total load compared to the other bolt diameter for both displacement 1.5 mm and 5 mm. In the same connection displacement the highest load per bolt is still obtained from using 7.9 mm bolt diameter but with the use of 4 pieces of bolts for almost all types of wood with the exception for punak and bitangur showing the highest values are obtained from 6 pieces of bolts. Bangkirai wood, kapur, punak, bintangur and meranti can be used as the main member in double shear connection by using bolt with diameter 6.4 mm, 7.9 mm and 9.5 mm because of fulfilling the requirements of PKKI (1961). Key words: Bolts, double shear connections, displacement, total load, load per bolt